Teaching language components to deaf/hard-of-hearing and cochlear implant users: a literature review - Lucchesi, Fernando Del Mando; Almeida-verdu, Ana Claudia Moreira (ABRAMO Associação Brasileira de Motricidade Orofacial, 2017)
ABSTRACT Cochlear implants are one of the possible ways for Deaf or Hard-of-Hearing (DHH) individuals to detect sounds and as a mean of insertion in the social, academic and work environments. Nevertheless, in many cases, the cochlear implant alone is not sufficient, demanding hearing and expressive language skills rehabilitation to optimize the device used. This study aimed at reviewing scientific articles that described empirical research with interventions and/or teaching methods of various language repertoires to deaf and hard-of-hearing cochlear implant users. The review was carried out in five scientific databases considering all periods. On the first phase, 156 articles were identified and from these, 24 publications were selected. After being read, these articles were categorized and analyzed as to the participants, teaching targets and procedures adopted. On the last stage of the research, 10 experimental studies were selected and analyzed regarding procedures and results, indicating important factors in teaching this population. The results point to the necessity of an increase of scientific production in the construction and evaluation of effective verbal repertoires teaching programs for cochlear implant users.

RESUMO O indivíduo com deficiência auditiva encontra no implante coclear um dispositivo de reabilitação da capacidade de detectar sons e de inserção no meio social, acadêmico e do trabalho. No entanto, em muitos casos, apenas o implante não é suficiente, sendo necessário investimento na reabilitação de habilidades auditivas e da linguagem expressiva para otimizar o uso do dispositivo. O presente estudo teve como objetivo revisar artigos científicos que apresentem estudos empíricos da aplicação de intervenções e/ou métodos de ensino de repertórios de linguagem diversos a população com deficiência auditiva e usuária de implante coclear. O levantamento foi realizado em cinco bases de dados em qualquer período. Na primeira etapa foram levantadas 156 publicações, e destes, 24 artigos foram selecionados. A partir da leitura, os artigos foram categorizados e analisados quanto aos participantes, alvos de ensino e procedimentos empregados. Na última etapa da pesquisa, 10 estudos experimentais foram selecionados e analisados quanto aos procedimentos e resultados, indicando alguns fatores importantes no ensino com esta população. Os resultados sugerem a necessidade de uma maior e mais sistemática produção científica na construção e avaliação de programas de ensino de repertórios verbais efetivos para a população usuária de implante coclear.
Ensino de componentes da linguagem a usuários de implante coclear: revisão da literatura
Keywords: Cochlear Implants; Teaching; Language Development; Review Literature as Topic; Implante Coclear; Ensino; Desenvolvimento de Linguagem; Literatura de Revisão como Assunto